The prognostic value of lymph nodes mRNA CXCL12 expression in the breast cancer - idha safitri; Irianiwati Widodo; Didik Setyo Heriyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Prognosis of breast carcinoma is influenced by age, tumor size, histological grade and type, lymph node status, as well as metastasic status. Chemokine receptor CXCR-4 with its ligand, CXCL-12, may play an important role in metastasis of breast carcinoma. However, the role of CXCL-12 mRNA as a prognostic factor and a therapeutic target of human breast cancer remains controversial. This study aimed to investigate the level of CXCL-12 mRNA expression in lymph nodes of patients with invasive ductal breast carcinoma and the difference within the prognostic factors. Axillary lymph nodes obtained from 50 cases of invasive ductal breast carcinoma, were divided into two groups, with and without lymph node metastasis. Each group consisted of 25 cases. Total RNA was extracted from formalin-fixed paraffin-embedded. The CXCL-12 mRNA expression was examined using qRT-PCR method. The mean differences between the two groups were analyzed using Mann-Whitney test. The differences between CXCL-12 mRNA expression and each prognostic factor ware analyzed using Mann-Whitney comparison test. CXCL-12 mRNA expression was significantly higher in the lymph node of patients with metastasis of breast carcinoma compared to the non-metastasis cases (p<0.01). There were significant differences between CXCL-12 mRNA expression with poorly histological grade (p=0.003), bigger primary tumor size (p=0.005) and age of ≥45 y.o (p=0.012) in the metastatic group, but there were no significant differences between both age of <45 and ≥45 y.o.This study suggests that the higher CXCL-12 mRNA expression level are associated with bigger tumor size and poor differentiation in breast cancer patient with lymph nodes metastasis